Effects of drying temperatures on physicochemical properties of germinated brown rice - Sunan Parnsakhorn (Songklanakarin Journal of Science and Technology (SJST), 2018)
This research has investigated the effects of varying drying temperatures on the physicochemical properties of germinated brown rice (GBR). The GBR samples were prepared in accordance with the prior research findings by which brown rice was soaked at 40 oC for 4 hrs prior to incubation at 40 oC and 90%RH for another 20 hrs. The resulting germinated brown rice was then divided into two groups and subjected to two different treatments: the steamed drying (SDR) and non-steamed drying (NSD) groups. The SDR group refers to the GBR samples steamed at 100 oC for 10 min prior to individually drying at temperatures of 20, 40, 80, and 160 oC, while the NSD group consists of the rice samples dried at the same temperatures without pre-steaming. The physicochemical properties of the GBR samples were subsequently analyzed to identify the optimal treatment condition. The findings revealed that the drying temperatures influenced the physicochemical properties of both GBR groups. The apparent hardness, water absorption and free fatty acids of both GBR groups were lower than those of the non-germinated brown rice, whereas their total lipids were higher. Besides, the higher drying temperatures had an adverse effect on the GABA content.